MathOverflow will be down for maintenance for approximately 3 hours, starting Monday evening (06/24/2013) at approximately 9:00 PM Eastern time (UTC-4).

4 deleted 722 characters in body

Hi miwalin!

First, let's agree that $x,y\geq 0$ for the definitions to make sense.

The solution is then actually quite simple: Let's assume $x^{2y}\geq y^{2x}\geq 0$. Then $x^{2y}+y^{2x}\leq 1$ is equivalent to $x^{4y}-y^{4x}\leq x^{2y}-y^{2x}$, i.e. $x^{2y}(x^{2y}-1)\leq y^{2x}(y^{2x}-1)$. By assumption, it suffices to show $0\geq x^{2y}-1\geq y^{2x}-1$, that is $x^{2y}\leq 1$ on the set $x+y=1$.

EDIT: next paragraph is corrected. I just computed the derivative wrong .

But this is standard: For instance, observe that $f(x):=x^{2-2x}$ takes values $f(0)=0, f(1)=1$ and its derivative $x^{2-2x}(\frac{2-2x}{x}-2\ln(x))$ is $\geq 0$, because $x^{2-2x}\geq 0$ and $\frac{1-x}{x}\geq \ln(x)$ for $x\in (0,1]$.

I hope this helped.proof attempt

3 added 9 characters in body

Hi miwalin!

First, let's agree that $x,y\geq 0$ for the definitions to make sense.

The solution is then actually quite simple: Let's assume $x^{2y}\geq y^{2x}\geq 0$. Then $x^{2y}+y^{2x}\leq 1$ is equivalent to $x^{4y}-y^{4x}\leq x^{2y}-y^{2x}$, i.e. $x^{2y}(x^{2y}-1)\leq y^{2x}(y^{2x}-1)$. By assumption, it suffices to show $0\geq x^{2y}-1\geq y^{2x}-1$, that is $x^{2y}\leq 1$ on the set $x+y=1$.

EDIT: next paragraph is corrected. I seem to have just computed the derivative wrong.

But this is standard: For instance, observe that $f(x):=x^{2-2x}$ takes values $f(0)=0, f(1)=1$ and its derivative $x^{2-2x}(\frac{2-2x}{x}-2\ln(x))$ is $\geq 0$, because $x^{2-2x}\geq 0$ and $\frac{1-x}{x}\geq \ln(x)$.ln(x)$for$x\in (0,1]$. I hope this helped. 2 added 85 characters in body Hi miwalin! First, let's agree that$x,y\geq 0$for the definitions to make sense. The solution is then actually quite simple: Let's assume$x^{2y}\geq y^{2x}\geq 0$. Then$x^{2y}+y^{2x}\leq 1$is equivalent to$x^{4y}-y^{4x}\leq x^{2y}-y^{2x}$, i.e.$x^{2y}(x^{2y}-1)\leq y^{2x}(y^{2x}-1)$. By assumption, it suffices to show$0\geq x^{2y}-1\geq y^{2x}-1$, that is$x^{2y}\leq 1$on the set$x+y=1$. EDIT: next paragraph is corrected. I seem to have computed the derivative wrong. But this is standard: For instance, observe that$f(x):=x^{2-2x}$takes values$f(0)=0, f(1)=1$and its derivative$x^{2-2x}\cdot\frac{4x-4}{x}\ln(x)$x^{2-2x}(\frac{2-2x}{x}-2\ln(x))$ is $\geq 0$, because $\ln(x)/x\leq 0, 4x-4\leq x^{2-2x}\geq 0$ for and $x\in [0,1]$.\frac{1-x}{x}\geq \ln(x)\$.

I hope this helped.

1